South African journalists’ conceptualisation of professionalism and deviations from normative liberal values - Ylva Rodny-Gumede (Communicare)
In this article the question is raised of what professionalism means in the context of South African journalism, and if there are deviations from ideas of professionalism as defined in normative liberal frameworks of the news media in terms of how South African journalists perceive their own role in society and as to how they define professionalism. The research is partially based on in-depth qualitative interviews with journalists from a crosssection of the South African news media, and asks questions about their own perceptions of professional values and their own role in society. The interview findings point to South African journalists articulating their role as one of neither watchdog nor lapdog – instead, the interviewees all articulate their role as based on competing imperatives, in which concerns for the audience and a broader articulation of the public interest take precedent over more liberal conceptualisations of the role of journalism in democracy.